Genes Software - extended and integrated with the R, Matlab and Selegen - Cruz, Cosme Damião (Acta Scientiarum. Agronomy, 2016)
The Genes Software is useful for analyzing and processing phenotypic and molecular data using different biometric models. In the current version we dispose routines to integrate it with three other softwares: the R, Matlab and Selegen. This version allows in plant and animal breeding complementary analyzes in several breeding research fields as genomic selection, prediction of genetic values, use of neural networks and Fuzzy logic. The Genes is important to estimate parameters for understanding biological phenomena necessary to make decisions and predict the success and viability of strategic selection. The original programme can be downloaded in Portuguese, English or Spanish with the specific literature from (http://www.livraria.ufv.br/) and the user guide from (http://www.ufv.br/dbg/genes/genes.htm and http://www.ufv.br/dbg/biodata.htm). The user has also support in the address www.facebook.com/GenesNews. The Genes is also integrated in the application softwares MS Word, MS Excel and Paint to efficiently import data and export results as numbers and figures.

O programa GENES é um software destinado à análise e processamento de dados fenotípicos e moleculares por meio de diferentes modelos biométricos. Na versão atual estão disponibilizadas rotinas de integração com o software livre R e com os aplicativos Selegen e Matlab. Esta integração possibilita análises complementares em áreas diversas do melhoramento genético incluindo a seleção genômica ampla, predição de valores genéticos, o uso de redes neurais, e a lógica Fuzzy. O uso do programa Genes é de grande importância em estudos genéticos aplicados ao melhoramento vegetal e animal, por permitir obter estimativas de parâmetros para entendimento de fenômenos biológicos e fundamentais em processo de tomada de decisão e na predição do sucesso e viabilidade da estratégia de seleção. O programa é obtido pela rede Internet (http://www.ufv.br/dbg/genes/genes.htm ou http://www.ufv.b/dbg/biodata.htm) e está disponível nos idiomas português, inglês e espanhol. Conta com literatura específica (http://www.livraria.ufv.br/) e um conjunto de arquivos de exemplos, tornando-o de fácil utilização. O apoio ao usuário é feito via rede social no endereço www.facebook.com/GenesNews. O programa GENES também está integrado aos aplicativos MS Word, MS Excel e Paint permitindo importar dados e exportar resultados, dados e figuras de forma simples e eficiente.
Keywords: Software; Statistical analyses; Genetic analyses; Quantitative genetic; Biometry